Search for polarized antiproton production - Grzonka, D.; Alfs, D.; Asaturyan, A.; Carmignotto, M.; Diermaier, M.; Eyrich, Wolfgang; Głowacz, B.; Hauenstein, F.; Horn, T.; Kilian, K.; Lersch, D.; Malbrunot-Ettenauer, S.; et al. (Hyperfine Interactions, 2019)
The production of antiprotons is studied in view of possible polarization effects as basis for a polarized antiproton beam. If antiprotons are produced with some polarization, a quite simple procedure for the generation of a polarized antiproton beam could be worked out. The experiments are performed at the CERN PS test beam T11 where secondary particles with momenta around 3.5 GeV/c are selected. The polarization analysis is performed by measuring the asymmetry of the elastic p̄ p-scattering in the Coulomb-nuclear interference region. The detection system includes Cherenkov and tracking detectors for the particle identification and the 3d track reconstruction. Details on the detection system and the status of the analysis are given.
CRIS-Team Scopus Importer:2019-05-09
Keywords: 24.70.+s; CNI; DIRC; Drift chamber; Elastic scattering; Polarized antiproton; Track reconstruction